Испарение химически опасных веществ с низкой температурой кипения - Popov В.; Il’yushonok Александр; Katkov В.; Leshenyuk Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
Evaporation of liquid having a low boiling point is considered after its spilling onto a surface as a result of an accident. Three modes of evaporation condition are described, which are realized in superheated, boiling and not boiling liquid. In the energy balance equation, which determines the evaporation process, heat transfer from underlying surface and from air, the absorption of shortwave solar radiation and atmospheric longwave radiation by liquid, as well as the emission of thermal radiation from a surface of liquid, is included. Examples of calculation of evaporation of the liquid are given under various atmospheric conditions.